Kebutuhan Energi Mekanik Mesin Perontok Sawit Dengan Motor Listrik Tiga Fasa Melalui Transmisi Sabuk-V Di Pabrik Kelapa Sawit - Nanda Kusuma; Busrizal Faisal; Rafael Remit Winardi (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2025)
A thresher is a crucial unit in a palm oil mill that separates loose fruit from fresh fruit bunches (FFB). Its performance is significantly influenced by the availability of mechanical energy transmitted from a three-phase electric motor through a V-belt system. This study aims to analyze the mechanical energy requirements of a thresher under varying FFB loads and electrical parameters. The research method employed field observation, current and voltage measurements, and energy consumption calculations. The results indicate that the greater the FFB load processed, the higher the motor's electrical current requirements. The maximum current was 49.84 A at 380 V, with a motor power of 20 kW. The highest load the machine can handle is 3,324 kg, with a kinetic energy requirement of 72,000 kJ. Analysis of the current-load relationship shows a linear pattern, confirming a direct relationship between increasing mechanical capacity and electrical energy consumption. These findings emphasize that matching electrical power to mechanical load capacity is crucial to prevent energy inefficiency and machine damage from overload. This research contributes to efforts to optimize energy consumption in palm oil mills by regulating input load, maintaining the V-belt transmission system, and implementing more efficient motor control technology.